Influence of imperfections on the out-of-plane flexural strength of post-tensioned masonry walls - Bean Popehn, Jennifer R.; Schultz, Arturo E. (Construction & building materials, 2013)
► Imperfections affect the nominal flexural strength of PTM walls. ► Unrestrained tendons exhibit a larger detrimental effect than restrained tendons. ► The influence of imperfections increases with wall slenderness. ► Code provisions providing tolerance limits reduce the effects of imperfections. The influence of imperfections on the response of simply-supported post-tensioned masonry (PTM) walls subject to out-of-plane loading is investigated. Two types of imperfections of the masonry and/or tendons are studied: a linear misalignment and an initial deflection defined using a sinusoid. Walls with a range of slenderness ratios are considered, in addition to walls with restrained and unrestrained tendons. By means of finite element studies, imperfections were found to affect the nominal flexural strength of the walls by as much as 10% for a linear imperfection and 20% for an initial deflection. However, the tolerance limits on the placement of masonry and post-tensioning tendons, coupled with the conservatism implicit in the nominal flexural strength formulas developed for design use in the US, appear to be sufficient to offset those differences, thus precluding consideration of accidental eccentricity for PTM walls.